1992
DOI: 10.1210/jcem.74.1.1530790
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, secretion, and metabolism in users of oral contraceptives.

Abstract: Studies of insulin employing the oral glucose tolerance test demonstrate marked differences between the effects of different oral contraceptives, but provide little insight into the underlying disturbances. We investigated the metabolic basis of these disturbances by computer modelling of iv glucose tolerance test glucose, insulin, and C-peptide concentration profiles. Insulin resistance, secretion, and metabolism were evaluated in 296 oral contraceptive users and 95 nonusers. Four estrogen/progestin combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
6

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 21 publications
2
41
1
6
Order By: Relevance
“…We assumed a background prevalence of 7% for PCOS among daughters of control women. None of the subjects was receiving hormonal (33), antihypertensive (34), or antidiabetic (35) medications, including 6 mothers with a history of diabetes and 27 with a history of hypertension.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed a background prevalence of 7% for PCOS among daughters of control women. None of the subjects was receiving hormonal (33), antihypertensive (34), or antidiabetic (35) medications, including 6 mothers with a history of diabetes and 27 with a history of hypertension.…”
Section: Methodsmentioning
confidence: 99%
“…50 However, supraphysiological doses of oestrogens, as achieved by administration of the oral contraceptive pill, increase insulin resistance. 51,52 Exogenous oestrogen increases SHBG concentrations, with studies in postmenopausal women demonstrating a larger increase with oral than with transdermal administration. 53 In postmenopausal women, oral oestrogen therapy is associated with a greater reduction in risk of developing type 2 DM than transdermal therapy.…”
Section: Shbg and Insulin Resistance: Cross-sectional Studiesmentioning
confidence: 99%
“…Many PCOS women are now believed to have insulin resistance (IR), and many studies have shown that oral contraceptives can cause deterioration of IR and several other metabolic, cardiovascular and inflammatory parameters. [1][2][3] Androgens themselves and the androgenic progestogen in many oral pills can induce or increase IR. 4,5 Pills containing antiandrogens, such as cyproterone acetate or drospirenone, are already available, but they are costly compared to the DSG-containing pill.…”
Section: Introductionmentioning
confidence: 99%